REGISTER PETANI PADI SAAT PANEN DI DESA TANJUNG MAJU KABUPATEN KETAPANG: KAJIAN SOSIOLINGUISTIK - Frans Jhorsmano; Amriani Amir; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problems in this study include the type of register, register function, and the form of descriptive text material to complement the speech of rice farmers at harvest time in Tanjung Maju Village, Ketapang Regency as learning Indonesian in the 2013 curriculum. Sociolinguistics. The purpose of this study was to describe the type of registers used by rice farmers during rice harvesting in Tanjung Maju Village, Sungai Laur District, Ketapang Regency to describe the register function contained in padai farmer registers at rice harvesting in Tanjung Maju Village. Sungai Laur Subdistrict, Ketapang Regency and explains the implementation of the use of the rice farmer register book at harvest in Tanjung Maju Village, Ketapang Regency in the description text as learning Indonesian in the 2013 curriculum. The method used is qualitative. The data source in this study is the Dayak Simpakng language spoken by informants in Tanjung Maju Village. The data collection techniques used were interview techniques, competent free listening techniques, recording techniques, and note taking techniques.Keywords: Rice Farmers during harvest in the Village of Tanjung Maju advenced, Speech Events, Register.